Model Based and Model Free Methods for Kinetic Study of Thermal Degradation of Cellulose Thiophosphinite Derivative - MALHOTRA, DEEPA; KUMAR, KRISHAN; DAHIYA, J.B. (Asian Journal of Chemistry, 2010)
Cellulose diethylamino ammoniumthiophosphinite (CEAAT) has been chosen for a study of its degradation behaviour from ambient temperature to 700 ºC using thermogravimetry. Cellulose diethylamino ammoniumthiophosphinite when heated in helium atmosphere, gives rise to higher char yield (45 %) as compared to cellulose (9.1 %) at 700 ºC. Kinetics was studied using model based and model free methods for degradation of CEAAT up to 700 ºC. After taking into account the values of activation energy and pre-exponential factor both obtained by model free methods and comparing these values with the values obtained by model based method. The diffusion controlled and random nucleation type mechanisms are found the most probable during thermal degradation of CEAAT.